The prevalence of general anxiety disorder and its associated factors among women's attending at the perinatal service of Dilla University referral hospital, Dilla town, Ethiopia, April, 2020 in Covid pandemic - Chalachew kassaw; Digvijay Pandey (Heliyon, 2020)
Background: Coronavirus is rapidly increasing in Ethiopia, and the number of perinatal service users at the hospital decreased due to the fear of contracting the virus. The mental health of a pregnant mother is vital for preventing pregnancy and birth-related complications. This study aimed to determine the magnitude and associated factors of General anxiety disorder among perinatal service users in Dilla University referral hospital, Dilla, Ethiopia. Methods: A hospital-based cross-sectional study was conducted among 178 respondents from April 6 – May 6, 2020. The sampling technique of this study was Consecutive sampling. Data were collected using a structured interview. General anxiety disorder (GAD-7) was used to determine the outcome variable. Logistic regression analysis and adjusted odd ratio at 95% CI and p < 0.05 was used to determine the statistically significant association between general anxiety disorder and its predictors. Result: A total of 178 respondents with a 100% response rate were enrolled in the study. The mean income of respondents was 1500 (±700) Ethiopian birr. The overall prevalence of general anxiety disorder (GAD) was 32.2%. Living in Rural area [AOR = 0.48; 95% CI: (0.25–0.9) P = 0.02∗], Primary level of education [AOR = 0.41; 95%CI:(0.21–0.75), P = 0.03∗], poor social support [AOR = 4.3995%CI:(2.29–12.53), P = 0.001∗∗] and primigravida [AOR = 3.05; 95% CI: (1.53–6.08), P = 0.001∗∗] were variables significantly associated with general anxiety disorder at 95% confidence interval, p < 0.05. Conclusions: This study found that nearly one-third of the respondents had general anxiety disorder. Therefore, working on the mental health impact of the pandemic among perinatal service users is an urgent solution to promote their physical, mental, and psychological health of a mother and her baby.